State of the art in tracheal surgery: a brief literature review - Ibrahim, Mohsen; Siciliani, Alessandra; Rendina, Erino Angelo (Multidisciplinary Respiratory Medicine, 2018)
Background: Tracheal surgery requires a highly specialized team of anesthesiologists, thoracic surgeons, and operative support staff. It remain a formidable challenge for surgeons due to the criticality connected to anatomical considerations, intraoperative airway management, technical complexity of reconstruction, and the potential postoperative morbidity and mortality. Main body: This article focuses on the main technical aspects and literature data regarding laryngotracheal and tracheal resection and reconstruction. Particular attention will be paied to anastomotic and non-anastomotic complications. Short conclusion: Results from literature confirm that, when feasible, laryngotracheal and tracheal resection and reconstruction is the treatment of choice in cases of benign stricture and malign neoplasm. Careful patient selection, operative planning, and execution are required for optimal results.